Rogue elements - Miller, John Jackson (Star trek. Picard., 2021)
The captain of La Sirena, Cristóbal Rios, on the run from outlaws, fortune seekers, power brokers and relic hunters, learns that a good crew is hard to find as he draws on a Starfleet legend's experiences when he stumbles upon a mystery.